On the Issue of State Support of Agriculture: Regional Aspect - Androsova, Irina V.; Melnichuk, Aleksandr V.; Bondaletov, Valery V.; Vinichenko, Mikhail V.; Duplij, Elena V. (International Journal of Economics and Financial Issues, 2016)
Agro-industrial complex (AIC) - a complex socio-economic system, which includes companies with different forms of ownership and management. State regulation should ensure the effective functioning of agro-industrial complex as a single mechanism, taking into account the equality of all forms of economic entities, based on the harmonization of their interests. In addition, AIC is complex and biotech system. In agriculture, the most important use natural means of production. Land, water, etc. On results of operations is greatly affected by climatic and meteorological conditions, which determine the risky nature of production in agriculture. Agriculture, in view of the fact that this industry is the most capital and energy-intensive, less attractive to investors and entrepreneurs. In its development of agriculture and food yields 33 processing industry, which uses imported raw materials, the volume of which is growing faster than domestic production. Therefore, state regulation and support the development of agro-industrial complex - a objective necessity of a market economy. Keywords: economy, agriculture, government support JEL Classifications: E20, O13, O38